Teaching technology to young learners: teachers’ individual competencies - Korkeaniemi, Arttu; Lindfors, Eila; Kiviranta, Leena (Springer Science and Business Media LLC, 2025)
Introducing technology education (TE) at an early age is essential in today’s digital world. It is not only important to teach students how to use technology but also to cultivate technological literacy, which is critical in increasingly technology-driven societies. Teachers play a pivotal role in enhancing the technological literacy of young learners (ages 5–8 in this study), and they require specific competencies to integrate technology into their daily practices across various educational settings. This study investigates the key individual competencies that teachers need to conduct TE for young learners by focusing the experiences of 12 teachers who participated in in-service TE training and conducted various craft, design, and technology (CDT) and science, technology, engineering, arts, and mathematics (STEAM) projects in their classrooms. The study uses the multidimensional adapted process (MAP) model for teaching as its theoretical basis; this model includes the individual and teaching competencies needed by teachers. The findings reveal that teachers must possess both a knowledge base and personal orientation towards technology. These two include different competencies—such as pedagogical content knowledge (PCK) and self-efficacy—that are interrelated and essential for conducting TE projects with young learners. Based on these findings, the study proposes a framework outlining the key individual competencies needed for providing TE to young learners. The framework aims to enhance the professional development of teachers in their initial teacher education and in-service training. We propose that future research should utilise this framework to promote TE that fosters technological literacy among young learners.